Fuzzy Implication on Mutation for Uncertain Paths - Paul, TN (International Journal of Computer Sciences and Engineering, 2025)
In real, network analysis have numerous uncertainties in the communication path. Uncertainties affect the possibility of mutation in the path due to the fuzziness of the interplay, error rate and environmental factors. The said paper works out the fuzziness in the mutation of path for the uncertain factors. It quantifies the performance of the mutation as well as the genetic algorithm. It provides fuzzy model to deals with the factors affecting the uncertainty of the shorter paths. Fuzzy implications are considered for different factors. The new edges formed during mutation are also dealt with fuzzy concept. This is a robust metaheuristic algorithm that defines the shorter path problem from a different plane using genetic and fuzzy tool. The transfer of packet is delayed due to natural and human issues like, disruption, natural calamity, and human error during installation etc. The work provides alternative paths to reach to the destination with the uncertain factors.